2005
DOI: 10.1111/j.1365-2133.2005.06459.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring patients on methotrexate: hepatic fibrosis not seen in patients with normal serum assays of aminoterminal peptide of type III procollagen

Abstract: The data presented support the view that follow-up liver biopsies, as recommended by published guidelines, for patients on long-term low-dose methotrexate can be avoided if PIIINP levels are consistently normal. This approach would have reduced the number of patients requiring biopsy in our series by 45%. The PIIINP assay will also be helpful in the management of patients on methotrexate in whom liver biopsy is contraindicated, and in patients with nonalcoholic steatohepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 32 publications
3
60
0
Order By: Relevance
“…91,92 In patients receiving methotrexate, PIIINP appears to be a useful test for the evaluation of liver injury. [93][94][95] …”
Section: Piiinpmentioning
confidence: 99%
“…91,92 In patients receiving methotrexate, PIIINP appears to be a useful test for the evaluation of liver injury. [93][94][95] …”
Section: Piiinpmentioning
confidence: 99%
“…According to those studies liver biopsies can be avoided when serial PIIINP measurements (once per 3 months) are normal. In case of abnormal PIIINP values without other conditions associated with elevated PIIINP levels, a liver biopsy should be performed [13, 14]. Performing a liver biopsy only in patients with an abnormal PIIINP resulted, according to the study of Maurice et al [14], in a 45% reduction of all liver biopsies and the study of Chalmers et al [13 ]in a sevenfold reduction, without important liver damage being missed.…”
Section: Discussionmentioning
confidence: 99%
“…In case of abnormal PIIINP values without other conditions associated with elevated PIIINP levels, a liver biopsy should be performed [13, 14]. Performing a liver biopsy only in patients with an abnormal PIIINP resulted, according to the study of Maurice et al [14], in a 45% reduction of all liver biopsies and the study of Chalmers et al [13 ]in a sevenfold reduction, without important liver damage being missed. Boffa et al [15 ]and Zachariae et al [8, 16, 17 ]also concluded that the chance to develop substantial liver fibrosis and the risks of missing significant liver damage are minimal in case of persisting normal PIIINP values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example is the collaboration among a number of enthusiastic dermatologists in district general hospitals in West Hertfordshire who questioned but then confirmed the value of serological testing for liver fibrosis as an alternative to liver biopsy in psoriasis patients receiving methotrexate. 13 In spite of the creditable past track record of NHS clinicians as researchers, the potential for them to continue to contribute to treatment development and assessment has been severely constrained by over-regulation of clinical research. This trend has been characterised by Charles Warlow as 'a threat to public health' .…”
mentioning
confidence: 99%